A study of bacterial cell immobilization in alginate gel beads for the production of Myo-Inositol Phosphates - Mohamad Puad, Noor Illi; Farouk, Abd Alaziem; Mohd. Salleh, Hamzah (IIUM Press, 2011)
A no\'el phyrale-degrnding enzyme namely PhyFAUIA I was purificd from a bacTerium i~lated from Malaysian wastewatcr. It is a pcriplasmaTic cnzymc and highly substrate-specific to phylaTe. The bacTerial cells were immobilized in alginate gel beads and iTS condition for preparaTion of myo-inositol phosphatcs was invcsligaled. The conditions for immobilizcd eclls were opTimized using dilTerem mcdia, residence Time and Temperature. Upon immob,lizalion. beads containing cells were sTored in groWlh medium at 4°C and Thc yicld can be reTained for more than 24 hours. The mechanism of reaction beTween phylaTe and PhyFAUIAI using immobilizcd cells was also invcsTigated and thcre were 2 possible paThways: (II PhyFAUlAl was seereted from the cells and went OUI from the beads to react Wilh phylatc. (2) PhyTate diffused Through lhc pores of alginate beads and reacTed WiTh phytasc locatcd inside the beads as well as aT The pcriplasmic OfThc cells. P, and IP were Then released from the beads.